Analisis Kebijakan Pendidikan Islam (Suatu Kajian Studi Letaratur Manajemen Pendidikan) - Ahmadi Ahmadi; Minnah El Widdah (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2022)
Abstract: Islamic education is an educational concept that has long existed in Indonesia, even before Indonesia's independence. Birth of Law No. 20 of 2003 concerning the National Education System became the starting point for the development of Islamic Education in Indonesia. This study uses a type of library research (library research) to analyze Islamic education and the law in Law no. 20 of 2003 concerning the National Education System. This is shown by the existence of several Islamic education positions in Law no. 20 of 2003, namely: 1) Islamic Education as an educational institution both formal, non-formal and informal whose existence is explicitly recognized; 2) Islamic education as material or subject of religious education as one of the subjects that must be given at the elementary to tertiary level; and 3) Islamic education as Islamic religious values (value), namely when Islamic values are found in the education system. However, in its implementation there are still problems that make the implementation of Islamic education less than optimal. So that in its implementation, the existence of Islamic education in Law no. 20 of 2003 (Sisdiknas) needs to be supported or spelled out in other regulations. Abstrak: Pendidikan Islam merupakan konsep pendidikan yang telah lama ada di Indonesia bahkan sebelum Indonesia merdeka. Lahirnya UU No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional menjadi pintu awal berkembangnya Pendidikan Islam di Indonesia. Penelitian ini menggunakan jenis penelitian studi kepustakaan (library research) untuk menganalisis pendidikan Islam dam UU Dalam UU No. 20 Tahun 2003 tentang Sistem Pendidikan Nasional. Hal tersebut ditunjukan dengan beberapa esistensi posisi pendidikan Islam dalam UU No. 20 Tahun 2003, yaitu: 1) Pendidikan Islam sebagai lembaga pendidikan baik formal, nonformal, dan informal yang diakui keberadaannya secara eksplisit; 2) Pendidikan Islam sebagai materi atau mata pelajaran pendidikan agama sebagai salah satu pelajaran yang itu wajib diberikan pada tingkat dasar sampai perguruan tinggi; dan 3) Pendidikan Islam sebagai nilai-niali ajaran agama Islam (value) yakni ketika ditemukannya nilai-nilai Islami dalam sistem pendidikan. Namun dalam pelaksanaanya masih terdapat problematika-problematika yang membuat pelaksanaan pendidikan Islam kurang maksimal. Sehingga dalam pelaksanaanya, eksistensi pendidikan Islam dalam UU No. 20 Tahun 2003 (Sisdiknas) perlu didukung atau dijabarkan dalam peraturan lain.